Foundations of unit theory of movers on continuous flows. Calculation of formula of thrust of the sail - Мамедов, Борис Шамшадович (Eastern-European Journal of Enterprise Technologies, 2012)
Are looked through the drawbacks of modern theory of air-jet engines, which are connected with a mistake theorem of the rising force of blowing profile, calculated by professor N.J.Gukovsky in 1912 year. According to N.J.Gukovsky the maximum pressure of blowing gase flow on the trough of blowing profile is situated there, where circulation of gase flaw (Г =t•ΔWu) has a maximum meaning, that is on the outlet edge on trough of blowing profile, and, correspond, zero pressure on inlet edge on trough of blowing profile, because on inlet edge Г =0, since ΔWu=0. This, static pressure gradient on trough of blowing profile, according to theorem of raising force of blowing profile, calculated by professor N.J.Gukovsky in 1912 year is directed against blowing gase flaw, what is in a straight contradiction with an experiment data just of the same modern theory of air-jet engines, which declare, that maximum pressure of blowing gase flaw on trough of blowing profile is in zone of inlet edge of blowing profile, and this maximum pressure is gradually lowered while blowing gase flaw movement to outlet edge of blowing profile, regulation thus, static pressure gradient, directed by the flaw, [3], p.68, pic.3.3.